Metabolic modulation induced by chronic hypoxia in rats using a comparative proteomic analysis of skeletal muscle tissue. - De Palma, S; Ripamonti, M; Vigano, A; Moriggi, M; Capitanio, D; Samaja, M; Milano, G; Cerretelli, P; Wait, R; Gelfi, C (2007)
Hypoxia-induced changes of rat skeletal muscle were investigated by two-dimensional difference in-gel electrophoresis (2D-DIGE) and mass spectrometry. The results indicated that proteins involved in the TCA cycle, ATP production, and electron transport are down-regulated, whereas glycolytic enzymes and deaminases involved in ATP and AMP production were up-regulated. Up-regulation of the hypoxia markers hypoxia inducible factor 1 (HIF-1alpha) and pyruvate dehydrogenase kinase 1 (PDK1) was also observed, suggesting that in vivo adaptation to hypoxia requires an active metabolic switch. The kinase protein, mammalian target of rapamycin (mTOR), which has been implicated in the regulation of protein synthesis in hypoxia, appears unchanged, suggesting that its activity, in this system, is not controlled by oxygen partial pressure.